The Sacred Text in Muhammad Arkoun’s Thought Between Dogmatic Background and Epistemological Opening - ayadi, abdelmalek; cherif, Rida (Journal of Social Sciences and Humanities, 2021)
This article seeks to reveal the truth of the sacred text as conceived by Arkoun by attempting to rid it of the sacred ideologies that enveloped it with thick calcareous layers that prevent us from reaching its original nature.Arcon uses a set of contemporary scientific methods within the framework of epistemological openness in order to stand on human nature. Before this analytical approach, in which we presented the relative medial nature of the sacred text as an open text to man, we presented the conceptual approach in which we have recorded some of the concepts as employed by Arkoun, and deliver us to reveal dogmatism fences that surround the sacred text.